-3=-4+5a-4a

Simple and best practice solution for -3=-4+5a-4a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=-4+5a-4a equation:


Simplifying
-3 = -4 + 5a + -4a

Combine like terms: 5a + -4a = 1a
-3 = -4 + 1a

Solving
-3 = -4 + 1a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1a' to each side of the equation.
-3 + -1a = -4 + 1a + -1a

Combine like terms: 1a + -1a = 0
-3 + -1a = -4 + 0
-3 + -1a = -4

Add '3' to each side of the equation.
-3 + 3 + -1a = -4 + 3

Combine like terms: -3 + 3 = 0
0 + -1a = -4 + 3
-1a = -4 + 3

Combine like terms: -4 + 3 = -1
-1a = -1

Divide each side by '-1'.
a = 1

Simplifying
a = 1

See similar equations:

| 7t^2-5t-6=0 | | 16x+3=9x+73 | | -5*a+(-5*b)=5 | | -5/8x=-60 | | ((m^(1/5))/((m^(4/5))(m^-(4)))=m^(a/b) | | 8d^2+6d+1=0 | | 5(.5-3)+3(.5+3)=2(.5)-3 | | 8u^2-9u-3=0 | | 3x^3+33x^2+90x= | | 2m^2+4m+2=0 | | 3x^3+6x=4x^2+8 | | x+2x+2= | | 6(1x-1x)=11x-2(x+2) | | 7.2-3y=5 | | 5r-5r=1 | | 7.1-3y=5 | | 5.2+y=10 | | 3x+2x-20+4x-20=180 | | 5.1+y=10 | | -49x^2+6=-7x | | 5v-2v=-24 | | -4-n-4n+15=0 | | 9y+9-9y=18-9y | | 5x^2-110x+105= | | -5x+15=7x-21 | | 7-3y=5 | | 1/2(10-2)-1/6(60-5) | | 0.5x+0.83=0.66x-0.25 | | -5(x-3)=7(x-3) | | 22p+2p+p= | | 160=x+(4x+10) | | 3x+4(600-x)=2200 |

Equations solver categories